Effects of concentrated urine on complications and plasma creatinine: a prospective study in elective non-cardiac surgery patients - Xie, Kai; Li, Yuhong; Zou, Wenjie; He, Rui; Hahn, Robert G. (Frontiers in Medicine, 2025)
ObjectivesThe urine concentration of metabolic end products increases in response to low habitual water intake or acute dehydration. We examined the impact of concentrated urine on surgical outcomes with special attention given to plasma creatinine levels.MethodsA prospective observational study was conducted involving 921 patients scheduled for non-cardiac major surgery. The degree of urine concentration was quantified prior to the surgery using a composite index (Fluid Retention Index, FRI) that reflects renal water conservation. Arterial pressure was monitored every 5 min during the operations. A perioperative increase in plasma creatinine of >50% or ≥26.5 μmol/L was designated as acute kidney injury (AKI).ResultsThe average operating time averaged 2.9 ± 1.3 h (mean ± SD) during which the mean arterial pressure was 5.2 ± 13.1 mmHg lower than the preoperative reading. Concentrated urine (FRI > 4.0) was present in just 7% of the patients, signifying that dehydration was infrequent. Univariate analysis showed that these patients still had extended gastrointestinal recovery time (p < 0.001), larger hemorrhages (5% vs. 1% > 500 mL; p = 0.047), and a heightened occurrence of fever (28% vs. 17%; p < 0.03). Multivariate analysis showed an extended gastrointestinal recovery time and smaller urine output despite receiving more crystalloid fluid (all correlations p < 0.001). Gradually higher FRI was associated with lower MAPs at baseline (p < 0.024). Postoperative AKI developed in only 1% of the patients, which made the study underpowered to detect a statistically significant relationship between concentrated urine and AKI (odds ratio 0.988, 95% confidence interval 0.980–0.996; p = 0.43).ConclusionPatients with concentrated urine before surgery had a lower urine output during surgery and a longer postoperative period of food intolerance and more often fever than patients with dilute urine. The occurrence of postoperative AKI was very low, which was probably due to the generally good hydration status.